TEACHERS’ STRATEGIES IN FACILITATING READING COMPREHENSION FOR STUDENTS WITH LIMITED READING SKILLS IN INCLUSIVE CLASSROOM: A QUALITATIVE CASE STUDY - Najla Regar; Emeliya Sukma Dara Damanik (JETAL: Journal of English Teaching & Applied Linguistic, 2026)
Students with limited reading skills often face difficulties in understanding English texts, particularly in inclusive classrooms where students have diverse learning needs. This study aimed to identify the strategies used by English teachers in facilitating reading comprehension for students with limited reading skills in inclusive classrooms and to describe the challenges encountered during the teaching process. This study employed a qualitative case study design involving two English teachers at a senior high school in Southeast Aceh, Indonesia. Data were collected through classroom observations, semi-structured interviews, and document analysis and were analyzed using the interactive model of Miles and Huberman. The findings revealed that the teachers employed six strategies: simplified texts, pre-teaching vocabulary, code-switching, scaffolding, reading aloud, and multimodal support. These strategies were implemented to facilitate reading comprehension for student with limited reading skills by providing instructional support, reducing language barriers, and increasing engagement in reading activities. The study also identified three major challenges, including limited facilities and technology, limited instructional time, and low student motivation. These findings provide practical insight for English teachers, schools, and education stakeholders in designing and implementing reading comprehension strategies that better address the diverse needs of students with limited reading skills in inclusive classroom.